Cardboard citizenship: realization of the right to health for the homeless population (Research, Society and Development, 2020)
To know the experiences and challenges faced by homeless people in the city of Pedreiras - MA to achieve access to civil health law, to know their experiences and searches for access to public health, to investigate the trajectory of seeking care with health services. the type of care offered by health professionals in the context of homeless people, where most of the interviewees have been on the street for a long time, motivated by their own desire, based mainly on the use of drugs and they do not have the habit of attending units health care, and only in a state of emergency do they go to hospitals, as regards the health aspects of the homeless population is the fact that they do not receive access to primary  care services, as they did not reveal having received any assistance in their living environment, and not even the incentive to go to the service, even though there are already specific public policies for health care for the population of street, it is necessary that the powers rethink the form of effective access, as they end up having no structure to offer a decent service to this population, lack of qualification and accessibility.